Risk Factors Associated With the Development of Nephropathy 10 Years After Diagnosis in Taiwanese Children With Juvenile-Onset Type 1 Diabetes—A Cohort Study From the CGJDES - Yang, Ching-Chien; Lin, Chia-Hung; Wang, Nan-Kai; Lai, Chi-Chun; Lo, Fu-Sung, The Chang Gung Juvenile Diabetes Eye Study Group; Chen, Tun-Lu; Chao, An-Ning; Chen, Kuan-Jen; Hwang, Yih-Shiou; Chen, Yen-Po; Chen, Yih-Hsin (Frontiers in Endocrinology, 2018)
OBJECTIVE To examine the risk factors for diabetic nephropathy (DN) 10 years after the diagnosis of juvenile-onset type 1 diabetes mellitus (T1DM) in a Taiwanese population. RESEARCH DESIGN AND METHODS This retrospective, observational, longitudinal cohort study of 224 patients with T1DM for > 10 years (mean duration 12.6 years) included participants from the Chang Gung Juvenile Diabetes Eye Study Group. The patients received a T1DM diagnosis before the age of 18 years and were treated at the pediatric endocrine department of Chang Gung Memorial Hospital in Taiwan. The epidemiological and laboratory data such as age, sex, duration of diabetes, self-reported smoking, blood pressure, lipid profiles, urinalysis, and glycated hemoglobin A1c (HbA1c) levels were collected from medical records retrospectively for investigating the relationship between the clinical parameters and the development of DN in T1DM RESULTS During follow-up, 44 of the 224 patients (19.6%) developed DN, of whom 61.4% were female. Cox proportional hazards model analysis indicated that the female (HR 3.40, 95% CI 1.66-6.96, p = 0.001), smoking (HR 3.60, 95% CI 1.28-10.10, p = 0.015), HbA1c level (HR 1.27, 95% CI 1.07-1.49, p = 0.005), diastolic blood pressure (HR 1.06, 95% CI 1.03-1.09, p < 0.001) were significantly correlated with DN after adjustment for multiple variables. The tight glucose control with multiple daily injections produced 49 % risk reduction (HR 0.51, 95% CI 0.26-0.98, p = 0.043). CONCLUSIONS The risk of DN in patients with juvenile-onset T1DM 10 years after the T1DM diagnosis was increased with female, smoking, high HbA1c, diastolic blood pressure levels and attenuated by intensive therapy.